Pulmonary involvement in inflammatory bowel disease - Yılmaz, Aydın (Baishideng Publishing Group Co., Limited, 2010)
AIM: To determine the relationship of pulmonary abnormalities and bowel disease activity in inflammatory bowel disease (IBD). METHODS: Thirty ulcerative colitis (UC) and nine Crohn’s disease patients, and 20 control subjects were enrolled in this prospective study. Detailed clinical information was obtained. Extent and activity of the bowel disease were established endoscopically. Each patient underwent pulmonary function tests and high-resolution computed tomography (HRCT). Blood samples for measurement of C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), angiotensin converting enzyme and total IgE were delivered by the patients. RESULTS: Ten (25.6%) patients had respiratory symptoms. A pulmonary function abnormality was present in 22 of 39 patients. Among all patients, the most prevalent abnormalities in lung functions were a decrease in forced expiratory volume in 1 s (FEV1), FEV1/forced vital capacity (FVC), forced expiratory flow (FEF) 25%-75%, transfer coefficient for carbon monoxide (DLCO), DLCO/alveolar volume. Increased respiratory symptoms score was associated with high endoscopic activity index in UC patients. Endoscopic and clinical activities in UC patients were correlated with FEV1, FEV1/FVC, and FEF 25%-75%. Smoking status, duration of disease and medication were not correlated with pulmonary physiological test results, HRCT abnormalities, clinical/endoscopic disease activity, CRP, ESR or total IgE level or body mass index. CONCLUSION: It is important that respiratory manifestations are recognized and treated early in IBD. Otherwise, they can lead to destructive and irreversible changes in the airway wall.